How to prove -(a+b) = (-a)+ (-b)

Asked on by jaxen28

1 Answer | Add Yours

mvcdc's profile pic

mvcdc | Student, Graduate | (Level 2) Associate Educator

Posted on

First of all, note that `-(a+b)` is equivalent to `-1*(a +b)` .

By the distributive property of multiplication, we have:

`(-1*a) + (-1*b)`

which can be simplified/written as:

`(-a) + (-b)` which is our desired expression.


Another solution:

`-(a+b) = -a - b = -a + (-b) = (-a) + (-b)` again, the desired expression.

We’ve answered 319,863 questions. We can answer yours, too.

Ask a question